2009
DOI: 10.1093/rpd/ncp154
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon measurements in areas of northern Greece with relatively high indoor radon concentrations

Abstract: Indoor radon concentrations were measured in 77 schools of the prefecture of Xanthi in northern Greece. The arithmetic mean radon concentration is 231 Bq m(-3) with a range between 45 and 958 Bq m(-3). Thirty five schools have mean radon concentration above 200 Bq m(-3) and nine schools have mean radon concentration above 400 Bq m(-3). From continuous radon gas measurements in the school with a relative higher radon concentration (958 Bq m(-3)) was deduced the 'true' radon concentration, defined as the radon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
1
6
1
Order By: Relevance
“…In the present work, a factor of 4 was measured between mean and "true" radon concentration in one school with a relatively low radon concentration. Previously, Clouvas et al (2009) reported a factor of 7. As expected, no correlation between radon gas concentration and indoor gamma dose rate was observed.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the present work, a factor of 4 was measured between mean and "true" radon concentration in one school with a relatively low radon concentration. Previously, Clouvas et al (2009) reported a factor of 7. As expected, no correlation between radon gas concentration and indoor gamma dose rate was observed.…”
Section: Resultsmentioning
confidence: 95%
“…Indeed there is an overestimation, but it is not a little overestimation, it is a very important overestimation. As an example, in the school with the higher annual radon concentration (958 Bq m À3 ), we (Clouvas et al, 2009) performed from 20 January 2009 up to 4 February 2009 radon measurements every 10 min. The AM radon concentrations when the school was in operation and when it was closed were 104 Bq m À3 and 866 Bq m À3 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 19 studied Prefectures, the Prefecture of Xanthi had the highest mean radon concentration (229 Bq m À3 ) and the highest percentage (42%) of schools with 222 Rn concentrations above 200 Bq m À3 . In a follow-up study, Clouvas et al (2009) measured indoor radon concentrations in 77 schools of the prefecture of Xanthi in winter. The arithmetic mean radon concentration was 231 Bq m À3 with a range between 45 and 958 Bq m À3 .…”
Section: Introductionmentioning
confidence: 99%
“…The differences are more pronounced between short-term measurement by active method and passive long--term method. For example, using short-term measurements with active method, Clouvas et al, 2009 found that: (a) in school with a high level of radon during school time, the concentrations were lower by a factor of 7 than when the school was closed; (b) in school with low levels, this difference was a factor of 4 [6]. Similar radon dynamic has been reported for Slovenian schools [7,8].…”
Section: Resultsmentioning
confidence: 55%